THE FUTURE OF SUSTAINABLE HOSPITALITY: GREEN PRACTICES SHAPING THE INDUSTRY - Gulnoza Xusanova Akram qizi (The latest news and research in education, 2025)
Sustainability in the hospitality sector has become a critical emphasis for both businesses and travelers as environmental concerns continue to influence global industries. This article investigates the industry's transformation by investigating the increasing demand for sustainable practices in hospitality, which is being driven by technology, eco-conscious accommodations, and responsible sourcing. The hospitality sector is increasingly incorporating green practices to cater to the demands of environmentally conscious consumers, including energy-efficient hotel designs, waste reduction strategies, locally-sourced culinary options, and ethical supply chains. Furthermore, we investigate the economic advantages of sustainability, emphasizing the potential for enhanced brand loyalty and cost-saving strategies. The article also discusses the obstacles that hospitality businesses encounter when attempting to implement sustainable initiatives, such as the complexity of the supply chain and the initial investment required. The article examines future trends, including circular economy principles and carbon-neutral hotels, underscoring that sustainability is not merely a trend but a fundamental transformation towards a more responsible and resilient industry. The hospitality industry's dedication to sustainability will be indispensable in determining its future as eco-conscious travelers become increasingly prevalent.